Redescription of Larval Development in Cultured Pearl Oyster Pinctada maxima - Jeane Siswitasari Mulyana; Achmad Farajallah; Yusli Wardiatno (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
Larval development plays a major role in efficient pearl culture. The cultured larvae will be later used for recipient and donor oysters in cultured pearl production. Larval developmental stage of silver lip pearl oyster Pinctada maxima has been reported by several studies. Those studies used female and male oyster parents directly taken from natural habitat.This study aimed to redescribe larval development of P. maxima from commercial pearl oyster culture farm in Indonesia. Larval development of this species whose parents are originated from selected groups in the pearl culture farm has not been reported yet, thus it is necessary to be described. This species undergoes specific larval developmental stage. The larvae were observed under microscope, and then the average shell length (SL) and shell height (SH) were measured. D-shaped veliger larva (77.4±0.3 µm SL; 65.4±1.1 µm SH) appeared 20 h after fertilization. Tenday-old larva (156.2±2.8 µm SL; 149.5±5.6 µm SH) had developed umbo region so it was called umbonal larva. Umbonal larva then developed further into plantigrade larva (411.3±9.8 µm SL; 380.5±6.9 µm SH) in 25 days after fertilization. Developmental stage and larval sizein P. maxima is similar with those observed in P. fucata and P. margaritifera. Keywords: growth, larva, plantigrade, shell, umbo, veliger